A model for a multi-size inland container transportation problem. (May 2016) - Funke, Julia; Kopfer, Herbert
Highlights: We introduce the multi-size inland container transportation problem. We formulate a mixed-integer program for the multi-size transportation problem. We implement and compare two objectives. We analyse the experimental results of instances which vary in size. It is the first model which is able to solve instances of this problem type optimally. Abstract: In the multi-size Inland Container Transportation Problem (mICT) trucks are able to transport up to two 20-foot or one 40-foot container at a time along routes with various pickup and delivery locations. A mixed-integer linear program for the mICT is presented using two alternative objective functions: minimization of the total travel distance and minimization of the total operation time of the trucks. The presented model is tested on instances which vary in size. Computational experiments show that by means of the presented model small problem instances can be solved optimally.